A random-sampling method as an efficient alternative to variational Monte Carlo for solving Gutzwiller wavefunctions. (7th December 2021) - Zhang, Feng; Ye, Zhuo; Yao, Yong-Xin; Wang, Cai-Zhuang; Ho, Kai-Ming
Abstract: We present a random-sampling (RS) method for evaluating expectation values of physical quantities using the variational approach. We demonstrate that the RS method is computationally more efficient than the variational Monte Carlo method using the Gutzwiller wavefunctions applied on single-band Hubbard models as an example. Non-local constraints can also been easily implemented in the current scheme that capture the essential physics in the limit of strong on-site repulsion. In addition, we extend the RS method to study the antiferromagnetic states with multiple variational parameters for 1D and 2D Hubbard models.